Latin America and the search for a coastal law: lessons from the legislative procedure in Colombia (2022)
In 2009, a network of scholars identified the legal framework associated with coastal management in eleven Latin American countries. They found an important lag in several countries, including Colombia. According to many scholars, a clear regulatory framework is of the utmost importance for integrated coastal management; however, the hurdles to reaching this goal have been poorly analyzed. This article aims to illustrate the challenges and barriers to legislate on coastal and marine issues in Colombia. The methodology and analysis used in this study can serve as an example to other Latin American countries. We combined comparative, documentary, and analytical research techniques to describe the current Latin American state-of-the-art legal framework. Additionally, from 16,224 gazettes (official records of the Congress of Colombia) we identified 80 bills concerning coastal and marine activities for a period of 17 years. However, only 2.1% of those bills addressed marine or coastal issues from the perspective of planning and management procedures. Instead the majority focused on social uses and economic activities. This research identified the difficulties that could be faced by a country in regulating its coast from an integrated perspective. These findings could support future procedures to approve coastal laws in Latin America and other countries on the world.